Analisis Faktor Risiko Keluhan MSDs pada Tenaga Pendidik dan Non Pendidik Sekolah Islam Ramah Anak Cilodong Depok Saat Melaksanakan Pembelajaran Jarak Jauh - Annisa Millenda Gunawan (2021)
The Covid-19 disease pandemic impacts the world of education. The change in the learning process to be distance learning increase musculoskeletal disorders. The purpose of this study was to analyze the risk factors for musculoskeletal disorders disorders (MSDs) on educators and non-educators Islamic Schools Child Friendly currently implementing distance learning. This study is quantitative with a cross-sectional study design and a sample size of 60 respondents. The sampling technique is total sampling. Data analysis was performed, namely univariate and bivariate with chi-square test. This analysis to see the relationship between work posture, duration of work, age, gender, IMT, and stress levels in the presence of complaints of MSDs. The results of this study showed factors related to MSDs complaints, namely work posture (p-value = 0.008; OR = 0.11), work duration (p-value = 0.042; OR = 4.2), and age (p- value = 0.045; OR = 0.2). Therefore, researchers recommend educators and non -educators to do stretching every 40 minutes, use ergonomic chairs with cushions, and provide working hours according to the age of the employee.